2009
DOI: 10.4161/cbt.8.10.8128
|View full text |Cite
|
Sign up to set email alerts
|

Leptin accelerates enterocyte turnover during methotrexate-induced intestinal mucositis in a rat model

Abstract: Gastrointestinal mucositis occurs as a consequence of cytotoxic treatment. In the present study, we tested whether leptin can protect gut epithelial cells from methotrexate (MTX)-induced intestinal damage. Non-pretreated and pretreated with MTX Caco-2 cells were incubated with increasing concentrations of leptin for 24 h. Cell proliferation and apoptosis were assessed using FACS analysis. Adult rats were divided into three experimental groups: Control rats; MTX-rats were treated with a single dose of MTX, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Various studies have demonstrated the potential benefits of LLLT in its ability to reduce the rates of WHO severe grade mucositis [121, 122]. Other novel methods and experimental approaches include a formulation containing the amino acid L-glutamine and the hormone, leptin; both have been shown to have a positive impact on the development of mucositis [123126]. …”
Section: Present Practice and Therapeutic Optionsmentioning
confidence: 99%
“…Various studies have demonstrated the potential benefits of LLLT in its ability to reduce the rates of WHO severe grade mucositis [121, 122]. Other novel methods and experimental approaches include a formulation containing the amino acid L-glutamine and the hormone, leptin; both have been shown to have a positive impact on the development of mucositis [123126]. …”
Section: Present Practice and Therapeutic Optionsmentioning
confidence: 99%
“…Use of LLLT, utilizing an InGaAlP diode laser at a wavelength of 660‐nm, on chemotherapy patients with various cancers, including non‐Hodgkin’s Lymphoma, showed lower rates of severe grade WHO mucositis (Silva et al , 2010). Other experimental approaches include the hormone, leptin, which may accelerate enterocyte turnover and has been shown to beneficially impact the development of mucositis in rats treated with methotrexate (Sukhotnik et al , 2009b).…”
Section: Mucositismentioning
confidence: 99%
“…Dihydrofolate reductase is an enzyme essential for DNA synthesis. In this way, DNA synthesis is impaired (3) and apoptosis takes place in the cells (3,36). While elevated Bax protein has been determined in MTX administrations, the level of Bcl 2 protein decreases (26).…”
Section: Discussionmentioning
confidence: 99%